The effect of environmental, social, and governance (ESG) on firm performance: the moderating role of country regulatory quality and government effectiveness in ASEAN - Sofik Handoyo; Syaiful Anas (Cogent Business & Management, 2024)
The research examines how Environmental, Social, and Governance (ESG) performance influences firm performance in the ASEAN region, focusing on how country regulatory quality and government effectiveness affect this relationship. The study uses a comprehensive dataset and finds that environmental and social performances do not directly impact firm performance significantly. However, governance performance has a notably positive effect on firm performance, highlighting the importance of sound governance practices. The study also identifies that the connections between environmental and social performance and firm performance are notably affected by country regulatory quality and government effectiveness. This suggests that the benefits of environmental and social initiatives on firm performance depend on the regulatory and governance environments in which firms operate. Similarly, the link between governance performance and firm performance is also influenced by these factors. These findings underscore the essential role of supportive regulatory structures and effective government practices in enhancing the positive effects of ESG initiatives on firm performance. Overall, this study enhances our understanding of ESG impacts within the ASEAN context and emphasizes the need to integrate ESG efforts with broader institutional support to achieve optimal firm performance.
Keywords: G34; K22; M14; O16; Q56; 650; ESG; ASEAN; regulatory quality; government effectiveness; firm performance